Answer:
x =
![(J-Hy)/(G)](https://img.qammunity.org/2022/formulas/mathematics/college/cpv2zthltm6kt1n80teuu9liejszaemgn4.png)
Explanation:
This question is from the topic subject of formula. It implies expressing x in terms of G, H y and J.
Given that: Gx + Hy = J
Subtract Hy from both sides to have;
Gx + Hy - Hy = J - Hy
⇒ Gx = J - Hy
Then divide both sides by G, so that we have;
x =
![(J-Hy)/(G)](https://img.qammunity.org/2022/formulas/mathematics/college/cpv2zthltm6kt1n80teuu9liejszaemgn4.png)
Therefore,
x =
![(J-Hy)/(G)](https://img.qammunity.org/2022/formulas/mathematics/college/cpv2zthltm6kt1n80teuu9liejszaemgn4.png)